Analytical Framework for End-to-End Delay Based on Unidirectional Highway Scenario. (4th June 2015) - Hassan, Aslinda; Ahmed, Mohamed H.; Rahman, M. A.
Abstract : In a sparse vehicular ad hoc network, a vehicle normally employs a carry and forward approach, where it holds the message it wants to transmit until the vehicle meets other vehicles or roadside units. A number of analyses in the literature have been done to investigate the time delay when packets are being carried by vehicles on both unidirectional and bidirectional highways. However, these analyses are focusing on the delay between either two disconnected vehicles or two disconnected vehicle clusters. Furthermore, majority of the analyses only concentrate on the expected value of the end-to-end delay when the carry and forward approach is used. Using regression analysis, we establish the distribution model for the time delay between two disconnected vehicle clusters as an exponential distribution. Consequently, a distribution is newly derived to represent the number of clusters on a highway using a vehicular traffic model. From there, we are able to formulate end-to-end delay model which extends the time delay model for two disconnected vehicle clusters to multiple disconnected clusters on a unidirectional highway. The analytical results obtained from the analytical model are then validated through simulation results.